Host dependence of the electron affinity of molecular dopants. Issue 1 (2nd October 2018) - Li, Jing; Duchemin, Ivan; Roscioni, Otello Maria; Friederich, Pascal; Anderson, Marie; Da Como, Enrico; Kociok-Köhn, Gabriele; Wenzel, Wolfgang; Zannoni, Claudio; Beljonne, David; Blase, Xavier; D'Avino, Gabriele
Abstract : Accurate molecular modeling reveal the surprisingly large impact of the solid-state environment on the electron acceptor levels of molecular dopants. Abstract : Charge carriers energetics is key in electron transfer processes such as those that enable the electrical doping of organic semiconductors. In this study, we take advantage of the quantitative accuracy of embedded GW calculations to perform a series of virtual experiments that allow measuring the electron affinity of p-type dopants in different host solids. Our calculations show that the energy levels of a molecular impurity strongly depend on the host environment as a result of electrostatic intermolecular interactions. In particular, the electron affinity of a dopant impurity in a given semiconductor is found to be up to 1 eV lower than that of the pure dopant crystal. This result questions the pertinence of the electron affinity measured for pure dopants in order to predict doping efficiency in a specific host. The role of the Coulomb electron–hole interaction for the dopant-to-semiconductor charge transfer and for the release of doping-induced charges is discussed.